Science in Silence - Büntgen, Ulf; Krusic, Paul J.; Di Cosmo, Nicola (ERDKUNDE, 2021)
Intellectual and cultural benefits from extended periods of self-isolation have a long history. The ongoing decline in academic freedom, however, distinguishes the coronavirus disease from previous crises. Despite the unprecedented political and economic challenges, as well as the devastating societal disruptions caused by the global COVID-19 pandemic, this study focusses on the fresh opportunities the current coronavirus restrictions offer to question extant academic models and paradigms, in the spirit of creating a more equitable and sustainable research system in the future.